Genome-Wide Identification of Direct Targets of ZjVND7 Reveals the Putative Roles of Whole-Genome Duplication in Sour Jujube in Regulating Xylem Vessel Differentiation and Drought Tolerance - Li, Meng; Hou, Lu; Zhang, Chenxing; Yang, Weicong; Liu, Xinru; Zhao, Hanqing; Pang, Xiaoming; Li, Yingyue (Frontiers in Plant Science, 2022)
The effects of whole-genome duplication span multiple levels. Previous study reported that the autotetraploid sour jujube exhibited superior drought tolerance than diploid. However, the difference in water transport system between diploids and autotetraploids and its mechanism remain unclear. Here, we found the number of xylem vessels and parenchyma cells in autotetraploid sour jujube increased to nearly twice that of diploid sour jujube, which may be closely related to the differences in xylem vessel differentiation-related ZjVND7 targets between the two ploidy types. Although the five enriched binding motifs are different, the most reliable motif in both diploid and autotetraploid sour jujube was CTTNAAG. Additionally, ZjVND7 targeted 236 and 321 genes in diploids and autotetraploids, respectively. More identified targeted genes of ZjVND7 were annotated to xylem development, secondary wall synthesis, cell death, cell division, and DNA endoreplication in autotetraploids than in diploids. SMR1 plays distinct roles in both proliferating and differentiated cells. Under drought stress, the binding signal of ZjVND7 to ZjSMR1 was stronger in autotetraploids than in diploids, and the fold-changes in the expression of ZjVND7 and ZjSMR1 were larger in the autotetraploids than in the diploids. These results suggested that the targeted regulation of ZjVND7 on ZjSMR1 may play valuable roles in autotetraploids in the response to drought stress. We hypothesized that the binding of ZjVND7 to ZjSMR1 might play a role in cell division and transdifferentiation from parenchyma cells to vessels in the xylem. This regulation could prolong the cell cycle and regulate endoreplication in response to drought stress and abscisic acid, which may be stronger in polyploids.